Minimally invasive plate osteosynthesis for clavicle shaft fractures. (1st June 2022) - Burkhard, M D; Michelitsch, C; Stillhard, P F; Müller, T; Sommer, C
Abstract: Objective: Whereas open reduction and internal fixation remains the surgical standard for displaced clavicle shaft fractures, the minimally invasive plate osteosynthesis (MIPO) technique has been introduced for multifragmentary, non-antomically reducible fractures, and unstable fractures with significant soft tissue injuries. Its advantages lie in the preservation of the vascular supply of the fracture zone and the preservation of the supraclavicular nerve. The aim of this study was to prove feasibility and share our experiences with this technique. Methods: In this single center retrospective case series, we analyzed all patients that underwent MIPO for displaced clavicular shaft fractures from 2001–2021. Patient history, fracture morphology and perioperative data were documented. Outcomes were assessed based on clinical and radiographic follow-up reports. Results: In total, 1128 clavicle osteosyntheses were performed, of which 908 (80.5%) were treated with a plate and 220 (19.5%) with titanium elastic nail (TEN). Of the 908 plate osteosyntheses, 43 (4.7%) were performed with the MIPO approach. Mean age was 44 ± 15 years, 83.3% were males and 79.1% were sports injuries. The fractures were categorized as AO/OTA type C injuries (n=26) in most patients, followed by A (n=9) and B (n=8). Two open (Gustilo I) and 41 closed fractures were noted (Tscherne 0=26; I=13, II=2). In seven patients (16.7%), the clavicle fractures were part of a severe polytrauma. Concomitant serial rib fractures and scapular fractures were found in 19 (45.2%) and 10 patients (23.8%), respectively. Length of surgery was 63 ± 28 min, and hospitalization was 4 ± 3 days (excl. polytraumas). 27 of the 43 fractures (62.8%) were clinically and radiographically followed up in our outpatient clinic, of which 26 (96.3%) healed with noticeable callus formation. In one case, a pseudoarthrosis was found two years after fracture treatment. Otherwise, all patients followed a remarkable postoperative course, were pain-free and able to return to work, most within five weeks. Conclusion: In this retrospective analysis, 96.3% of the clavicle shaft fractures treated with MIPO healed in a timely manner. The MIPO technique is feasible and plausibly advantageous for distinct fracture and injury patterns (i.e. multifragmentary fractures or unstable fractures with soft tissue injuries). Future comparative studies are warranted to clarify our observations.